"Like–Likes–Like" strategy for the design of electron transport materials and emitters with facilitated interlayer electron transport and improved efficiency. Issue 8 (26th January 2022) - Wu, Yibing; Lin, Rui; Iqbal, Mudassir; Jin, Yaocheng; Huo, Yanping; Ouyang, Xinhua
Abstract : A novel strategy of "Like–Likes–Like" is proposed to design and synthesize the electron transport materials (ETMs) and emitters for high-performance electroluminescent devices, including similar characteristics of structures, molecular orbitals, and ground/excited-states. Abstract : A novel strategy of "Like–Likes–Like" is proposed to design and synthesize the electron transport materials (ETMs) and emitters for high-performance electroluminescent devices, including similar characteristics of structures, molecular orbitals, and ground/excited-states. Two novel compounds based on this strategy, PI–DPO–TPA and PI–DPO–PI, were successfully synthesized and applied to the fabrication of efficient organic light-emitting diodes (OLEDs). Both compounds cooperate well with each other from the perspective of exciton dynamics when respectively deposited as the non-doped OLED emitter and the ETM layers. Therefore, the devices exhibit an extremely low turn on voltage (2.0 V) and high efficiencies (18.87 cd A −1, 16.91 lm W −1, and 8.45%). In comparison, the control device with traditional ETM layers ( i.e. TmPyPB) shows a relatively poor performance (4.5 V, 12.32 cd A −1, 4.02 lm W −1, and 4.20%). Furthermore, electron/hole-only devices, magneto-electroluminescence, and transient absorption spectra determine the contribution from the boosted formation of hot excitons, rather than the simply enhanced transport of a low-lying electron. The findings open a novel avenue to prepare ETMs and emitters for highly-efficient OLEDs.